Законність притягнення до адміністративної відповідальності за правопорушення, передбачене ст. 130 КУпАП: ретроспективний аналіз - Чишко, К. О.; Chyshko, K. O.; Чишко Катерина Олександрівна (Вісник Харківського національного університету внутрішніх справ. – 2021. – № 4 (95). – С. 179-187, 2021)
Проаналізовано приписи законодавчих актів, унаслідок яких керування транспортним засобом у стані алкогольного, наркотичного чи іншого сп’яніння або під впливом лікарських препаратів, що знижують увагу та швидкість реакції, визнається не адміністративним, а кримінальним проступком. Зроблено висновок, що притягнення до юридичної відповідальності за вказане правопорушення в такому контексті суперечить змісту принципу законності, що може призвести до порушення прав і свобод громадян щодо неправомірного застосування до них заходів примусу та незаконного притягнення до юридичної відповідальності.

The provisions of a number of legislative acts have been analyzed in detail, as a result of which driving under the influence of alcohol, drugs or other intoxicants or under the influence of drugs that reduce attention and speed of reaction is recognized as not an administrative but a criminal offense. Some intermediate conclusions have been made. Driving under the influence of alcohol, drugs or other intoxicants or under the influence of drugs that reduce attention and speed of reaction, in the period from July 1, 2020 to March 17, 2021: 1) was recognized not as an administrative offense, but as a criminal offense; 2) detection, termination and documentation of such a criminal offense was carried out mainly by patrol police officers, and not by investigators, as required by current criminal procedure legislation; 3) a report on an administrative offense and other administrative -procedural documents were drawn up upon the fact of committing a criminal offense; 4) the prosecution of a person did not take place as a result of a pre-trial investigation, but within the framework of proceedings in cases of administrative offenses. It is proved that the above facts contradict the content of the principle of legality, in particular, "ignored" the rule of compliance with current legislation, including the rules of criminal procedure, which is the main component of the content of the principle of legality. It is noted that the actions of the police in identifying persons driving under the influence of alcohol, drugs or other intoxicants or under the influence of drugs that reduce attention and speed of reaction, were directed at a specific individual, so we should talk about violations of the rights and the freedoms of citizens with regard to the unlawful application of coercive measures and illegal prosecution. It was stated that the clarification provided in this regard by the Committee on Law Enforcement of the Verkhovna Rada of Ukraine is neither a source of law nor a normative legal act and is not binding, but instead serves a recommendatory function, therefore, the involvement of persons for committing a specific criminal offense under the procedure of proceedings on administrative offenses has no legal grounds.

Проанализированы предписания законодательных актов, в результате которых управление транспортным средством в состоянии алкогольного, наркотического или иного опьянения или под влиянием лекарственных препаратов, снижающих внимание и быстроту реакции, признается не административным, а уголовным проступком. Заключено, что привлечение к юридической ответственности за указанное правонарушение в таком контексте противоречит содержанию принципа законности, что может привести к нарушению прав и свобод граждан относительно неправомерного применения к ним мер принуждения и незаконного привлечения к юридической ответственности.
Legality of bringing to administrative responsibility for an offense under Art. 130 Code of Ukraine on Administrative Offenses: retrospective analysis
Keywords: Адміністративне право та процес. Administrative Law and Procedure. Административное право и процесс; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; Історія. History. История; керування транспортним засобом у стані алкогольного, наркотичного чи іншого сп’яніння або під впливом лікарських препаратів, що знижують увагу та швидкість реакції; адміністративне правопорушення; адміністративний проступок; кримінальний проступок; адміністративна відповідальність; кримінальна відповідальність; провадження у справах про адміністративні правопорушення; досудове розслідування; дізнання; керування транспортним засобом; алкогольне сп’яніння; наркотичне сп’яніння; административный проступок; уголовный проступок; административная ответственность; управление транспортным средством; алкогольное опьянение; administrative offense; administrative misdemeanor; criminal misdemeanor; administrative liability; criminal liability; proceedings on adminis trative offenses; pre-trial investigation; inquiry; driving; alcohol intoxication; drug intoxication